Paratextual satire in the lettered city of Lima (Revista de Crítica Literaria Latinoamericana, 2014)
This essay proposes a detour through some colonial and nineteenth-century Limenian satiric texts that parody the conditions of access to the material format of the book, as the mainstream modality of publication of the lettered culture. From a conceptual framework that integrates a post-colonial perspective with other contemporary theoretical devices, the objective of this article is to detect in those parodie thresholds certain skeptical intellectual positions towards the idea of the lettered clerk, as much as to suggest an alternative genealogy for a critical practice that questions the official conventions for official discursive authorization.
Keywords: lettered city; parody; satire; book; paratexts; costumbrismo; museum